Pola Asuh Pengasuhan Orang Tua Dalam Memberikan Pendidikan Seks Kepada Anak Di UPT SDN 218 Gresik - Linda Novita Sari; Mulyadi; Barudin (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2022)
Every child is born into the world with a state of nature that has the potential to be born with religion and morals. The nature of each child will be different from other creatures, but nature will not be able to develop if there is no guidance and care from the closest people, the closest people, namely their parents who will provide primary education for each of their children before taking education, therefore parents must understand their position as the first teacher for their baby. The environment that has an important role for children's development is the family, this is where the child will be raised and the child will get his education, the parents themselves are the language, social and religious teachers for their children, because a father is the one who whispers the first call to prayer and iqomah in the ear of the child. his son. Sex life needs proper guidance and direction, so that later sex education will run well and be in accordance with religious teachings and the norms that apply in society. This behavior arises because most parents do not understand how to teach good sexual behavior, they just let their children find out for themselves when they grow up. The focus of the problem is what is the role of parents in providing sex education to fifth grade children at UPT SD Negeri 218 Gresik?, What forms of sex education are given by parents to fifth grade children at UPT SD Negeri 218 Gresik?, and what are the factors supporting and inhibiting factors in providing sex education to fifth grade children at UPT SD Negeri 218 Gresik?. And aims to know parenting parenting style in providing sex education to children. The approach that the author uses in this study is qualitative through natural settings (natural conditions), primary data sources, and more data collection techniques on observation, in-depth interviews and documentation with qualitative data analysis, including data reduction, data display, conclusions, and check the validity of the data. The form of parental involvement in providing sex education is that they supervise children, maintain child relationships, and provide advice for children not to do negative things that can harm themselves and provide support for children to always be enthusiastic about learning.